EFFECTS OF GAMMA-RADIATION ON POLY ISOBUTYLENE - BHOSALE, R.R.; DAHINDE, P.S.; KADAM, J.Y.; TATE, B.T.; BHOSLE, G.B.; DHONDE, S.P. (Innovare Journal of Sciences, 2020)
Radiological parameters such as Mass attenuation coefficient (μm), effective atomic numbers (Zeff), electron densities (Neff), total cross-section (σt) & electronic cross-section (σe) have been computed and investigated for poly-isobutylene using NaI (Tl) scintillation counter and XCOM program. The gamma ray photons were detected by using NaI (Tl) detector with resolution of 8.2 % at 662 keV, using radioactive gamma ray sources 57Co, 133Ba, 137Cs, 54Mn, 60Co and 22Na. Values of μm for the poly-isobutylene decrease with increasing energy. An experiment is done to avail the radiological data on poly- isobutylene and to check the effects of gamma radiation produced on material with different energy ranges. It is found from the present investigation that the investigated results found immense importance in radiation industry, dosimetry, polymer industry etc.